PWE-164 Assessment of Helicobacter pylori in iron deficiency anaemia: do we do this?. (28th May 2012) - Daker, C; Haji-Coll, M; van Someren, N; Besherdas, K
Abstract : Introduction: Globally iron deficiency anaemia (IDA) is responsible for over two billion cases. In the western world, an estimated 2–5% of adult men and post menopausal woman suffer with IDA. GI loses account for many cases and patients will undergo endoscopy to exclude pathology here. Recent evidence suggests that infection with H pylori (HP) should be considered despite the absence of peptic ulcer disease or other bleeding lesions in the GI tract. Hypothesised mechanisms for HP causing IDA are: chronic gastritis causing active bleeding, so iron is lost, achlorhydria decreasing iron absorption, the possibility that HP itself directly acquires iron so competing with the host, and also the possibility of an anaemia of chronic disease. Methods: The study aim was to determine whether patients with IDA referred for an gastroscopy (OGD) had a rapid urease test (CLO test) performed to confirm infection with HP. This was a single centre, retrospective analysis of consecutive patients endoscoped for IDA over 1 year upto January 2011. The endoscopy report was scrutinised for the performance of the CLO test and if performed the result was noted. Results: 194 Of 473 (41%) patients undergoing OGD for IDA had their CLO test obtained. Of these 27 of 194 (5.7%) were positive with 167 of 194 negative CLO tests. Conclusion: In this study, 59% of patients endoscopied for IDA did not have a HP test. We may be missing a simple treatable cause for IDA in the upper GI tract within this group of patients. Of those who were not tested (270) 71 exhibited other significant pathology (angiodysplasia, gastric/colonic cancer, peptic ulcers). The association of IDA with HP is not universally recognised and we believe may be the reason as seen in this study not tested for in the absence of peptic ulcer disease or another cause for bleeding when endoscoping patients for IDA. We recommend routine testing (and eradication if detected) of HP in patients IDA undergoing OGD. In addition, testing and eradicating for HP may also reduce the risk of development of gastritis, peptic ulcer, MALToma and gastric cancer in those found to have the bacteria. Competing interests: None declared.